Питання українських етнічних теріторій у працях Володимира Кубійовича - Власюк, О. (Народна творчість та етнографія, 2005)
This article is dedicated to the work of geographist, demographist and editor of "Encyclopedia of Ukrainian Studies" - Volodymyr Kubiyovych who did not receive enough attention because of his public work during Second World War as an organizer of military division "Halychyna". The author of this article is trying to do the analysis of scientific work of V. Kubiyovych and devoted to Ukrainian ethno-geography and it's contemporary meaning for better understanding of economical and political development of Ukraine.